2009
DOI: 10.1021/jo901742d
|View full text |Cite
|
Sign up to set email alerts
|

Polyaza Cryptand Receptor Selective for Dihydrogen Phosphate

Abstract: A hexaamine cage with pyridyl spacers was synthesized in good yield by a [2+3] Schiff-base condensation followed by sodium borohydride reduction. The protonation constants of the receptor as well as its association constants with Cl(-), NO(3)(-), AcO(-), ClO(4)(-), SO(4)(2-), H(2)PO(4)(-), and H(2)AsO(4)(-) were determined by potentiometry at 298.2 +/- 0.1 K in H(2)O/MeOH (50:50 v/v) and at ionic strength 0.10 +/- 0.01 M in KTsO. These studies revealed that although dihydrogen phosphate is less charged than su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 35 publications
3
39
0
Order By: Relevance
“…[7] All solvents and chemicals were reagent-grade quality, commercially purchased and used as supplied, except for 1,3,5-tris(aminomethyl)-2,4,6-triethylbenzene and 2,6-pyridinedicarbaldehyde which where prepared according to literature methods. [19] KNO 3 , Cu-A C H T U N G T R E N N U N G (NO 3 ) 2 ·2.5H 2 O and CuA C H T U N G T R E N N U N G (ClO 4 ) 2 ·6H 2 O were analytical-grade quality, commercially purchased and used as supplied.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] All solvents and chemicals were reagent-grade quality, commercially purchased and used as supplied, except for 1,3,5-tris(aminomethyl)-2,4,6-triethylbenzene and 2,6-pyridinedicarbaldehyde which where prepared according to literature methods. [19] KNO 3 , Cu-A C H T U N G T R E N N U N G (NO 3 ) 2 ·2.5H 2 O and CuA C H T U N G T R E N N U N G (ClO 4 ) 2 ·6H 2 O were analytical-grade quality, commercially purchased and used as supplied.…”
Section: Methodsmentioning
confidence: 99%
“…With the increase of the amount of copper to 1.0 equiv (Figure 1 b), dinuclear species start to form and they are the predominant species at Cu 2 + /pyr 2:1 ratio (Figure 1 c). The stability constant corresponding in KTsO (Ts = tosyl) and T = 298.2 K. [7] 2 + by 2.74 log units due to the charge repulsion between the two metal ions, which are in close proximity, besides the statistical factor. Insertion of a third copper ion is even more disfavoured due to the buildup of positive charge, which results in a formation constant of only 4.3 log units.…”
Section: Potentiometric Studiesmentioning
confidence: 99%
“…Similar studies were conducted with pyridine-containing cryptand derivative 143 . 238 The presence of hydrogen bond donor (ammonium) and hydrogen acceptor (pyridine) units was expected to impart selectivity for inorganic phosphate over other anions. Under conditions identical to those used for studies with receptor 142 , a strong preference for hydrogenphosphate over sulfate, acetate, nitrate, and chloride was observed near neutral pH in the case of receptor 143 .…”
Section: Major Phosphate-binding Functionalitiesmentioning
confidence: 99%
“…In fact, to the best of our knowledge, this compound has the highest SO 4 2− /NO 3 − selectivity reported for systems able to work in media with a water content of 50% or more. 9,10,14a,d,e,f,g,i,m Curiously, unlike what was found in the previous binding studies performed with the H n xyl n+ and H n pyr n+ receptors, 9,10 the H n pyrr n+ receptor binds to H n PO 4 (3−n)− giving rise to several receptor to anionic substrate stoichiometries (1 : 1, 1 : 2 and 2 : 1). This can be related to the fact that, unlike the mentioned receptors, the H n pyrr n+ receptor has in each entrance of the cavity six potential hydrogen bond donors and four positive charges, thus being likely that these interactions are enough for tight binding of a H n PO 4 (3−n)− anion without the need for full encapsulation.…”
Section: Anion Binding By the Receptor H N Pyrr N+mentioning
confidence: 85%
“…9,10 The protonated forms of the compound with m-xylyl spacers (xyl) revealed a high selectivity for sulfate in the presence of several monocharged anions, 9 while in the receptor with pyridyl spacers ( pyr) the presence of hydrogen bond acceptors in the form of pyridyl nitrogen atoms enhanced the affinity for hydrogen phosphate. 10 These studies showed that small structural changes can lead to an appreciable impact on the selectivity pattern of the receptors. Roelens et al described a triethylbenzene-capped macrobicyclic receptor containing pyrrolyl spacers ( pyrr, Scheme 1), which specifically recognizes β-glucopyranosides in organic medium.…”
Section: Introductionmentioning
confidence: 99%